Hubungan Pengetahuan Dan Sikap Ibu Dengan Pemakaian Alat Kontarsepsi Implant - Rizawati (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2023)
Family planning is an attempt by a husband and wife to regulate the desired number and spacing of children. The business in question is contraception or pregnancy prevention and family planning. The basic principle of contraceptive methods is to prevent male sperm from reaching and fertilizing a woman's egg. This study aims to determine the relationship between maternal knowledge and attitudes and the use of implantable contraceptives at the Lubuk Begalung Community Health Center in 2023. This research is an analytical study with a cross sectional study design. The population in this study was all PUS family planning acceptors at the Lubuk Begalung Community Health Center in April 2023, namely 157 people. The sample obtained was 61 people. Data analysis used univariate and bivariate analysis with the Chi Square test. The results of the study showed that there was a relationship between maternal knowledge and the use of contraceptive implants (p= 0.008). There is a relationship between attitudes and the use of contraceptive implants (p= 0.000). Thus, it is recommended that mothers take the time to attend counseling held by health workers at the Community Health Center about family planning services so that they can increase mothers' knowledge and attitudes about implantable contraceptives. Keywords: Knowledge; Attitude; KB Implant